Analisis Karakteristik Responden, Jenis Jamban, dan Kepemilikan Jamban Sehat di Lingkungan IX Kelurahan Belawan I Kecamatan Medan Belawan - Meutia Nanda; Apzur Rohimah Putri; Sakina Sumantri; Saskia Khairina; Aja Mutiara Arini (Jurnal Ilmiah Wahana Pendidikan, 2023)
One indicator of PBHS is the availability of latrines that meet health needs and protect the environment from the spread of disease. Based on Indonesia's 2019 health profile, 72.3% of families use permanent healthy latrines, while 21.76% still practice open defecation (BABS) (RI Ministry of Health, 2020). Based on the 2015 Medan PKK, the number of latrines that met the health requirements was 283,577 and 1,266,985 people (86%) used them. This research was conducted with the aim of knowing the characteristics of the respondents, types of latrines, and ownership of healthy latrines in Neighborhood IX, Belawan I Village, Medan Belawan District. This type of research is descriptive quantitative, namely describing the characteristics of respondents, types of latrines, and ownership of healthy latrines in Neighborhood IX Belawan 1 Village in 2023. The variables in this study are the types of latrines and the condition of community latrines. The population in this study were all households in Environment IX, the sample was 90 households. Based on the results of research with Univariate, it was found that as many as 79 people (88.8%) had goose neck latrines, while cemplung latrines were 11 people (12.2%), and ownership of healthy latrines was still low.